2021
DOI: 10.3390/antiox10081160
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Drug Treatment That Reduces Mitochondrial Iron and Reactive Oxygen Levels Recovers Insulin Secretion in NAF-1-Deficient Pancreatic Cells

Abstract: Decreased insulin secretion, associated with pancreatic β-cell failure, plays a critical role in many human diseases including diabetes, obesity, and cancer. While numerous studies linked β-cell failure with enhanced levels of reactive oxygen species (ROS), the development of diabetes associated with hereditary conditions that result in iron overload, e.g., hemochromatosis, Friedreich's ataxia, and Wolfram syndrome type 2 (WFS-T2; a mutation in CISD2, encoding the [2Fe-2S] protein NAF-1), underscores an additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…They showed that treatment with the ferroptosis inhibitor ferrostatin-1 improved the cellular growth of NAF-1-repressed pancreatic cells. The authors concluded that the reduction of the mitochondrial iron levels could be used as a therapeutic route for patients with WS2 within the in vitro study [ 38 ]. Human studies are needed in order to verify the efficacy of molecules that block ER stress-induced apoptosis in the treatment of WS2.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that treatment with the ferroptosis inhibitor ferrostatin-1 improved the cellular growth of NAF-1-repressed pancreatic cells. The authors concluded that the reduction of the mitochondrial iron levels could be used as a therapeutic route for patients with WS2 within the in vitro study [ 38 ]. Human studies are needed in order to verify the efficacy of molecules that block ER stress-induced apoptosis in the treatment of WS2.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) were measured using a Seahorse XFp, Agilent, cell mito-stress analyzer (Agilent Technologies, Inc.) with the XF Cell Mito Stress Kit and XF Glycolysis Stress Kit (Agilent Technologies, Inc.), as previously described ( 26 ), and according to the manufacturer’s instructions ( 40 ). MDA-MB-231 cells (25,000) were grown to ∼80% confluence in complete medium overnight before the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown on eight-well Permanox chamber slides and, upon reaching ∼80% confluence, were fixed in 2.5% glutaraldehyde and 2% paraformaldehyde in 0.1 M cacodylate buffer (pH 7.4) for 2 h at room temperature, then prepared for transmission electron microscope (TEM) imaging as described in detail in refs. 18 and 26 . Results were evaluated from 5 to 10 different cells randomly selected, averaged over 10 to 20 fields per cell; at least 100 to 200 mitochondria were counted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations